Development of a therapeutic approach for hereditary diseases with prime editing: A study on Alzheimer's disease. (December 2021) - Tremblay, Guillaume; Rousseau, Joël; Happi‐Mbakam, Cedric; Guyon, Antoine; Tremblay, Jacques P
Abstract: Background: The amyloid precursor protein (APP) plays a role in the pathophysiology of Alzheimer's disease. Excess cleavage by β‐secretase enzyme leads to the accumulation of β‐amyloid peptides. In contrast, a rare variant of the APP gene (A673T) decreases cleavage by β‐secretase. However, inserting this mutation with gene editing technology is a challenge. Our hypothesis is that prime editing allows a significant editing rate while inducing few off‐target mutations in the cell leading to a significant reduction in the amount of pathological peptides produced. The objective of this study is to achieve a permanent insertion of the A673T mutation by prime editing and obtain evidence of the reduced Aβ peptides accumulation in vitro . Method: Prime editing guide RNAs (pegRNA) were constructed according to different protospacer adjacent motifs (PAM) around the A673T mutation by varying the length of the primer binding site (PBS) and the reverse transcriptase template (RTT) sequence. Initially, one guide was used on the target gene (PE2). Afterwards, additional guides were used to favor DNA editing (PE3, PE3b). Different techniques were used to optimize editing, such as adding valproic acid, repeated transfections, modifying the PAM and the structure of the prime editor. The mutation was introduced in HEK 293T cells and later in neurons derived from fibroblasts of patients with Alzheimer's disease. The results were quantified by Sanger and deep sequencing. Result: Prime editing demonstrated precise editing in up to 64% in HEK 293T cells (Figure 1) with no notable off‐target mutations within the target window. In future experiments, the level of Aβ40‐42 peptides will be measured in the derived neurons. Conclusion: Our approach aims to demonstrate the potential of prime editing in the development of a treatment for Alzheimer's disease based on the protective effect of A673T. Our project also aims to evaluate optimization methods for prime editing.